A Multi‐Responsive MXene‐Based Actuator with Integrated Sensing Function. Issue 10 (12th February 2022) - Zhao, Tingting; Liu, Hai; Yuan, Li; Tian, Xuemin; Xue, Xianyang; Li, Tongkuai; Yin, Luqiao; Zhang, Jianhua
Abstract: Soft actuators have demonstrated promising applications in artificial muscles, bionic robotics, smart apparatus, and beyond. Nevertheless, most of the current soft actuators only present actuating features without any real‐time sensory feedbacks, which may prohibit the timely correction of actuation error leading to the damage of the systems and target objects especially in some interactive applications. Here, a multi‐responsive actuator with self‐sensing function is enabled by a bilayer structure composing of MXene coated‐paper and polyethylene. This actuator can be triggered by multi‐stimuli and performs large deformation with low power consumption but high response speed because of the remarkable photothermal and hygroscopic performance of MXene. Meanwhile, this actuator can detect its own deformation with an amplified sensing signal on the basis of the synergetic strain‐ and stimulus‐resistance response of the MXene coated‐paper. It is demonstrated that this actuator can not only serve as a multi‐responsive switch to monitor the environmental temperature and humidity, but also as a smart gripper. This multi‐responsive actuator with self‐sensing function provides a potential application in the field of soft robotics, intelligent switch, and bionic prosthesis. Abstract : A multi‐responsive actuator with self‐sensing function is presented based on MXene, paper, and polyethylene. This actuator can not only perform large deformation with low power consumption and high response speed triggered by multi‐stimuli, but also detect its own deformation with an amplified sensing signal on the basis of the synergetic strain‐ and stimulus‐resistance responses of the MXene coated‐paper.